Green Economy in the Transport Sector A Case Study of Limpopo Province, South Africa - Odiyo, John Ogony; Bikam, Peter Bitta; Chakwizira, James (Springer International Publishing : Imprint: Springer, 2022)
This open access book is interdisciplinary and provides cross-sectoral and multi-dimensional exploration of sustainable development and transportation in South Africa. Drawing on work from different disciplines, the book contributes not only to academia but also seeks to inform urban and regional policy with the view of contributing to the national aspirations of South Africa as espoused in the National Development Plan (NDP), 2030, National Spatial Development Framework (NSDF) Draft (2019), National Climate Change Adaptation Strategy (NCASS) Draft (2019), Green Transport Strategy for South Africa (2018-2050), and National Transportation Plan (NATMAP), 2050. Adopting a multi-dimensional assessment, the book provides a background for co-production concerning climate change, sustainable development, and transportation in the Global South. The book contributes in its analysis of the institutional and legislative framework that relates to the climate change, skills and knowledge transfer, sustainable development, and transportation in South Africa, as these are responsible for the evolution of the green economy and transport sector in the country. The connections among different sectors and issues such as environment, transport modes, technology innovation, vehicle management and emission control, skills and knowledge transfer, legislative and policy framework, and the wider objectives of the sustainable development goals (SDGs), especially goals 11 to 13. The success stories relating to climate change, sustainable development, and transportation in South Africa are identified together with the best possible practices that may inform better environmental, urban and regional planning, policy, practice, and management.